Design and Analysis of a Dynamic Space-Code Multiple Access with Large Area Synchronous Scheme Using the Smart Antenna System - Ng, Chee Kyun (2007)
The most important property in wireless systems, when it comes to increase the system capacity and spectrum efficiency, is eliminating interference. Code Division Multiple Access (CDMA) is considered interference-limited system. Spatial filtering using smart antenna has emerged as a promising technique to improve the performance of cellular communication systems; hence, Space Division Multiple Access (SDMA) has recently received increasing interest in improving the performance of wireless systems. These interference-limited systems are susceptible to time of arrival (TOA) and angle of arrival (AOA) of individual user signals, thus, a non-uniform traffic can severely degrade the performance of CDMA and SDMA systems. In this thesis, new approach of the joint multiple access system arising from the combination of CDMA and SDMA systems is designed, and its system performances are then investigated.